2(0.6x+x)=

Simple and best practice solution for 2(0.6x+x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(0.6x+x)= equation:


2(0.6x+x)=0

We simplify the equation to the form, which is simple to understand
2(0.6x+x)=0

Simplifying terms in parentheses
2*(+1.6x)=0

Reorder the terms in parentheses
+(+3.2x)=0

Remove unnecessary parentheses
+3.2x=0

We move all terms containing x to the left and all other terms to the right.
+3.2x=0

We simplify left and right side of the equation.
+3.2x=0

We divide both sides of the equation by 3.2 to get x.
x=0

See similar equations:

| (3k-3)(7k+7)= | | -8=p-5 | | -10b+2b+b=0 | | 5x+17x-8=180 | | 2(1.2)= | | (-76)+(-84)= | | (3x-6)(3x-6)=0 | | 27-9x=4x+8 | | 4(x+9)+5x= | | 2x-5=?(x+4) | | (-15)+(-7)= | | 21x^4=2+x^2 | | 2-8x/1 | | 4(x+5)=3(x-6)+x | | -2(7-y)+4=44 | | 5/16*40n | | 6b^2-40=-8b+2b^2 | | .2-y=-.05x | | (x+9)(x-5)/(5x+4) | | -17+x/8=15 | | -2.6d-3.4d= | | 3(4x-6)=3(4x-3) | | 5/4=-5/3+s | | 23/4x=67/8 | | -4(5t-3)+8t=7t-2 | | (4x-6)=3(4x-3) | | x+6/5+x+3/x=3 | | 7y+5=-6y-21 | | 2z+2=2-2z | | 6x+20=4x-36 | | 4r+7=-43 | | n^2+n=2n |

Equations solver categories